GCex: A Visual Analytics Approach for Interactive Exploration of Geochemical Models. (August 2015) - De Lucia, Marco; Jatnieks, Janis; Sips, Mike
Abstract: GCex is a graphical tool implementing a Visual Analytics approach to support interactive exploration of geochemical models. It encodes many-to-many input/output relationships by the simple yet effective approach called Stacked Parameter Relation (SPR). GCex assists in the setup of simulations, model runs, data collection and results exploration, greatily enhancing the user experi- ence in tasks such uncertainty and sensitivity analysis, inverse modeling and risk assessment. While in principle model-agnostic, the toolchain currently supports the geochemical code PHREEQC. For further information and download refer to the project site: http://www.gfz-potsdam.de/en/section/geoinformatics/projects/gcex/.